Ectopic Tooth in Mandibular Canal, Maxillary Sinus, and Mandibular Condyle - Mert Akbas; Zülfikar Karabıyık; Altan Varol (Case Reports in Dentistry)
Eruption of tooth into place other than tooth-bearing region is defined as ectopic eruption. Although ectopic eruption of tooth is rare, there have been cases in the maxillary sinus, mandibular condyle, nasal cavity, chin, palate, and orbital floor. Due to ectopic teeth’s rarity and lack of consensus for ıts treatment, incidence was entitled to be added to literature and discussed. It was reported that odontogenic tumors and cysts can develop around the ectopic tooth. Thus, ectopic teeth can be followed up regularly in case of no signs and symptoms. If the patient has unusual orofacial pain, undiagnosed nasal discharge, maxillary sinusitis, preauricular pain, preauricular fistula, trismus, and lip paresthesia, the patient should be evaluated in terms of ectopic tooth. Whether the patient has signs and symptoms related to ectopic tooth, early intervention for the removal of ectopic tooth along with accompanying lesion is the treatment of choice. Specialists choose intervention way based on their experience. When selecting the intervention, minimally invasive and less morbid way should be preferred. Intraoral approach rather than extraorally should be the first choice to prevent unesthetic scar and damage to facial nerve.